Grasping at Context: Cross Language Qualitative Research as Secondary Qualitative Data Analysis - Temple, Bogusia; Edwards, Rosalind; Alexander, Claire (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2006)
Research with people who are not fluent in the dominant language of the research endeavour often involves working with interpreters/ translators or researchers who can speak the relevant minority languages. They conduct the interviews and provide the written data used for analysis in a language other than the original. However, this kind of cross language research is often presented as if it is the analysis of primary data rather than the re-construction of it. We argue that analysis of cross language data shows some strong similarities with secondary data analysis. Questions about the relevance of the context in which data are produced are central to both cross language research and secondary qualitative data analysis. We illustrate our arguments using a research project that examined user views of interpreters and discuss how we dealt with the issue of context in analysing data that were collected by others and produced in languages we did not speak.URN: urn:nbn:de:0114-fqs0604107